Catalyst Free Synthesis of Thioamides from Pyrazole Aldehydes using DMSO as Solvent - Perci, S. Helen; Gunsundari, K.; Monisha, P.; Jayanthi, S. (Asian Journal of Chemistry, 2023)
A straightforward synthetic procedure for thioamides has been developed at 100 ºC using pyrazole aldehyde, a secondary amine, precipitated elemental sulphur and DMSO as solvent. The Willgerodt-Kindler reaction was successfully carried out by increasing the mole ratio of the precipitated sulphur and amine derivatives. The synthesized thioamides derivatives were characterized by 1H and 13C NMR, FT IR, HRMS spectrometric techniques. This method has various advantages, including high yields, a relatively rapid reaction time and the ability to operate in catalyst-free conditions.